Patrones de asentamiento en la Bética romana: Un estudio sobre la romanización desde el análisis arqueológico espacial - Moreno Escobar, María del Carmen (BAR International, 2025)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on the BAR Digital platform. What impact did the process of Romanization have on the landscapes and territories of ancient Hispania? This book examines the transformations of Baetica through a rigorous study of Western Sierra Morena and the Lands of Antequera, two key regions for understanding this historical period. The research adopts an innovative perspective that integrates spatial analysis and landscape study to examine the transition between the Second Iron Age and the Roman Imperial era. Through the systematic application of statistical methods and quantitative spatial analysis, the study establishes solid empirical foundations for understanding the territorial dynamics and social transformations of ancient communities. This methodology allows for the precise identification and analysis of patterns of continuity and change in spatial organization, providing new evidence about the complex relationships between local populations and their environment during this crucial period in the history of the Iberian Peninsula.